Gasification and Co-gasification Low-rank Coal with Biomass - Asri Gani; Ichiro Naruse (Syiah Kuala University, 2012)
Recently, there has been significant research interest in cogasification of coaland various types of biomass blends to improve biomass gasification and syngasproduction. In addition, ash present in biomass catalyses the gasification of coal. This experiment was conducted on the cogasification of various types of coal and biomass using drop tube gasifier under two sets temperatures 1173 and 1273K respectively. Most of the reactions are considered as endothermic, the heat input is needed to conduct the reactions. The additions of biomass to NL coal during co-gasification give no effect on gasification, since the reaction is endothermic. The increasing temperature from 1173 to 1273K only give small increase in the yield gas and efficiency due to the short of residence time